2007
DOI: 10.1074/jbc.m701610200
|View full text |Cite
|
Sign up to set email alerts
|

Insights into How CUB Domains Can Exert Specific Functions while Sharing a Common Fold

Abstract: Procollagen C-proteinase enhancers (PCPE-1 and -2) are extracellular glycoproteins that can stimulate the C-terminal processing of fibrillar procollagens by tolloid proteinases such as bone morphogenetic protein-1. They consist of two CUB domains (CUB1 and -2) that alone account for PCPE-enhancing activity and one C-terminal NTR domain. CUB domains are found in several extracellular and plasma membrane-associated proteins, many of which are proteases. We have modeled the structure of the CUB1 domain of PCPE-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 54 publications
(78 reference statements)
0
52
1
Order By: Relevance
“…Interestingly, the CUB domain region alone is sufficient to promote enhancement (4,10). We have shown that the triple helix of procollagens is not required for tolloid stimulation (6) and have identified several residues in CUB1 that seem to play a major role in the PCPE-procollagen interaction (11). Of note, when the calcium-binding site in CUB1 is disrupted, interaction with the C-terminal part of procollagen III is completely abolished, * This work was supported by the Ré gion Rhô ne-Alpes, the European Com-locating one possible interaction site on loops 5, 7, and 9 of CUB1.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the CUB domain region alone is sufficient to promote enhancement (4,10). We have shown that the triple helix of procollagens is not required for tolloid stimulation (6) and have identified several residues in CUB1 that seem to play a major role in the PCPE-procollagen interaction (11). Of note, when the calcium-binding site in CUB1 is disrupted, interaction with the C-terminal part of procollagen III is completely abolished, * This work was supported by the Ré gion Rhô ne-Alpes, the European Com-locating one possible interaction site on loops 5, 7, and 9 of CUB1.…”
mentioning
confidence: 91%
“…1A). CUB1NTR and CUB2NTR were produced with the QuikChange XL site-directed mutagenesis kit from Stratagene using the cDNA of human PCPE-1 inserted into the pCEP4 vector (Invitrogen), in-frame with an 8-histidine C-terminal tag (known as PCPEhis) (11). 5Ј-Phosphorylated primers were designed to delete residues 150 -275 to obtain CUB1NTR (numbering according to human full-length PCPE-1, including the signal peptide) and residues 26 -149 to obtain CUB2NTR.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to high homology to its family member PCPE1, homology with PCPE2 was found with several proteins containing CUB domains including the protein encoded by the Cubulin gene, BMP-1, and other members of the astacin family (14). The two CUB domains near the N terminus are the most conserved regions of the protein with the C-terminal NTR domain less well conserved.…”
Section: Pcpe2 Shares Sequence Homology With Proteins Containing Cub mentioning
confidence: 99%
“…The cDNA encodes a 415-amino acid protein that has 43% identity to the type I procollagen C-proteinase enhancer protein (PCPE1) (13). PCPE2, like PCPE1, contains two CUB (complement C1r/C1s, Uegf, Bmp1) domains, which are thought to be important in protein-protein interaction (14) and binding to the COOH-terminal propeptide of type I procollagen leading to the C-terminal processing of fibrillar procollagens by tolloid proteinases such as bone morphogenetic protein-1 (BMP-1) (13). In addition, the recent finding identifying BMP-1 as the key enzyme responsible for the cleavage of pro-apoAI into its mature form (15) raises the intriguing possibility that PCPE2 alone or in combination with BMP-1 participates in the processing of proapoAI and therefore influence the biogenesis of HDL.…”
mentioning
confidence: 99%
“…A subset of CUB domains appears to require Ca 2ϩ for optimum binding activity (16). The most N-terminal BMP1 CUB domain (C1) may play a role in imparting "chordinase" activity, or ability to cleave chordin (17), a substrate described below.…”
Section: B/tp Structurementioning
confidence: 99%